(untitled) (Nordic Journal of African Studies, 1995)
At the heart of democratic instability in most African countries is the fact that the state operates in a largely amoral milieu which makes it possible for politicians and other managers of state to abuse their positions in pursuit of private ends. This paper examines the origins and manifestations of this amoral milieu, and the ways in which it leads to a pervasive belief that the state is neither credible nor capable of pursuing the collective good of citizens. This exacerbates the endemic legitimacy crisis which has characterized African statehood since colonial times. The paper shows how amoral familism is linked with the legitimacy crisis and argues that democratic stability will be difficult to attain for as long as the amorality of the political order remains.